Upregulated Acute Systemic Inflammation-Related Genes based on Endotoxin Exposure Provide “Survival Benefit” or Create “High Risk of Death” in Leukaemia and Colon Cancer - Gizem Ayna Duran (European Journal of Biology)
Objective: Although endotoxin exposure has been shown to trigger innate immune responses and promote cancer, it has also been shown to prevent cancer formation. In our study, survival analysis was performed to determine whether the upregulated genes triggered by endotoxins have hazardous effects on cancers or provide a survival benefit. Materials and Methods: Gene intensity values of control and bacterial endotoxin-administered individuals were obtained from the Gene Expression Omnibus database. Using the R “Linear Models for Microarray Data” package, differentially expressed gene analyses were conducted to determine genes that differ between healthy and bacterial endotoxin-administered samples. “ShinyGo 0.80” web-based tool was used to determine the disease types indicated by these genes. The “Kaplan-Meier Plotter” web-based tool was used to conduct survival analysis. Results: Genes that create an innate immune response to bacterial endotoxin exposure and are upregulated differently than in individuals without exposure were identified. According to gene enrichment analyses, the two main types of cancer identified were leukaemia/lymoma and colon cancer. We detected that MLF1, STAT5B, and BCL3 genes led to poor survival; however, the ARHGAP26 gene was protective for acute myeloid leukaemia patients. In the case of colon cancer, SMAD7 and TLR2 genes were determined as leading to “high risk of death”. Conclusion: Once the systemic inflammation-related genes identified in our study are confirmed through laboratory experiments in samples taken from solid tissue in the case of colon cancer and at the level of genes obtained from blood samples in leukemias, genetically targeted treatments will also be possible.